2012
DOI: 10.1055/s-0031-1298334
|View full text |Cite
|
Sign up to set email alerts
|

Heat Exposure ofCannabis sativaExtracts Affects the Pharmacokinetic and Metabolic Profile in Healthy Male Subjects

Abstract: The most important psychoactive constituent of CANNABIS SATIVA L. is Δ (9)-tetrahydrocannabinol (THC). Cannabidiol (CBD), another important constituent, is able to modulate the distinct unwanted psychotropic effect of THC. In natural plant extracts of C. SATIVA, large amounts of THC and CBD appear in the form of THCA-A (THC-acid-A) and CBDA (cannabidiolic acid), which can be transformed to THC and CBD by heating. Previous reports of medicinal use of cannabis or cannabis preparations with higher CBD/THC ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 27 publications
1
50
0
Order By: Relevance
“…Preparations taken orally (capsules, oral‐mucosal sprays and imbued food/liquid consumables) have a much lower peak THC plasma concentration compared to inhalation and a longer lag to peak concentration ( t max ) of between 60 and 120 minutes . They are subject to both gastric hydrochloric acid degradation and extensive first pass metabolism resulting in a much lower systematic bioavailability of THC compared with inhaled preparations . A large number of studies have examined the gastrointestinal bioavailability of oral intake heavy metals through food, drinking water and complementary medicine.…”
Section: Resultsmentioning
confidence: 99%
“…Preparations taken orally (capsules, oral‐mucosal sprays and imbued food/liquid consumables) have a much lower peak THC plasma concentration compared to inhalation and a longer lag to peak concentration ( t max ) of between 60 and 120 minutes . They are subject to both gastric hydrochloric acid degradation and extensive first pass metabolism resulting in a much lower systematic bioavailability of THC compared with inhaled preparations . A large number of studies have examined the gastrointestinal bioavailability of oral intake heavy metals through food, drinking water and complementary medicine.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14] Notes: a COA results that were based on dry materials used in preparation of final product; these products were not used in final calculations of percentage of company COA. Company reported COA bolded numbers represent COA analysis from the same company we utilized in this study (#11, 18,25). Label claim % numbers bolded and italicized were products that only contained a CBD label claim as the primary cannabinoid and no total cannabinoid claims for comparative purposes.…”
Section: Discussionmentioning
confidence: 99%
“…20,22 It is likely that this is intentional as CBDA has been associated with an antiinflammatory effect and is thought to be involved in improved bioavailability of cannabinoids. [23][24][25] The remainder of the products and the two higher CBDA products also contained CBD as the primary cannabinoids with a range of 0-54 mg/mL or gram and a median of 10 mg/mL or gram. In fact, there are few products that have over 20 mg/mL or gram (6/29) or 50 mg/mL (3/29) or gram of CBD or total cannabinoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to avoid conflicting pharmacological reports, several authors have indicated that other plant cannabinoids need to be considered when evaluating cannabis effects (Eichler et al, 2012;Mechoulam, 2005;Turner, 1974). Our review shows that in most occasions other psychoactive cannabinoids are not even analyzed.…”
Section: Evaluating the Role Of Other Cannabinoids But 9-thcmentioning
confidence: 99%